Juventude negra, subjetividade, ensino médio e mercado de trabalho, um levantamento bibliográfico das publicações entre os anos 2000 e 2020 - Evangelista, Noely Thais (2022)
That research purpose to map studies on black youth, high school, and the job market. Based on the limits imposed by the context of the pandemic caused by COVID-19, this research is characterized as a bibliographic study on the subject adopted in Brazilian research with a cut between the years 2000 and 2020. The texts were selected to identify an intersection between the themes, totaling 44 theses, dissertations, and articles. The BDTD and Scielo databases were analyzed to locate and explore the writings on the subject considered changes in the country's social and formative structures. The study on education and education goes beyond the training processes in High School integrated to the perception of young blacks and blacks as possibilities in the face of their expectations about the job market. However, there is a reflection on issues that can be thought about individuals, without a school of work that considers their subjectivity and without job prospects that consider their subjectivity and without work prospects after the day of reproduction going and without work prospects future of denial and naturalization of this context of inequalities.